Crowdfunding Campaign Project on Infak.in Platform as an Effort to Increase Donations (Case Study of the Campaign to Defend Palestine) - Oktandi, Orlin Luvena; Imaroh, Iklil; Novrin, Khairani Azizah (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
Digital transformation has reshaped the way philanthropic organizations in Indonesia manage fundraising. Recognized as the most generous nation in the CAF World Giving Index, Indonesia offers a strong foundation for enhancing donation practices through technology. This study explores the “Defend Palestine” crowdfunding campaign launched by Laznas LMI on the Infak.in platform, aiming to analyze strategies that influence donation growth and donor trust. The research employed qualitative methods, using semi-structured interviews with Laznas LMI digital marketing staff and documentation analysis over a five-month period. The campaign was developed through pre-production, production, and post-production stages, combining storytelling, emotionally driven narratives, and influencer marketing. Teh Yunda Faisyah, a public figure with significant social media reach, was engaged as a spokesperson to strengthen credibility and increase visibility. The findings reveal that donations on the Infak.in platform rose steadily during the campaign’s ten-week observation, supported by clear narratives and influencer involvement. Data analysis showed a return on investment (ROI) of 109%, highlighting that the campaign generated nearly twice the revenue compared to costs. This demonstrates that integrating digital crowdfunding strategies with trust-building mechanisms can effectively improve philanthropic fundraising outcomes in Indonesia.